Expression of CD44 on bile ducts in primary sclerosing cholangitis and primary biliary cirrhosis. Issue 10 (1st October 1999) - Cruickshank, S M; Southgate, J; Wyatt, J I; Selby, P J; Trejdosiewicz, L K
Abstract : AIM: To examine expression of CD44, a transmembrane glycoprotein involved in lymphocyte homing and activation, in inflammatory liver diseases. METHODS: Formalin fixed, paraffin embedded tissues were obtained from normal, uninvolved liver from patients undergoing partial hepatectomy for metastatic carcinoma (9) and transplant hepatectomy specimens from patients with primary biliary cirrhosis (12), primary sclerosing cholangitis (8), autoimmune hepatitis (3), hepatitis C (3), and secondary sclerosing cholangitis (1). Expression of CD44 (using antibodies to three core epitopes), HLA-DR, and lymphocyte phenotypic markers was studied by immunohistochemistry. RESULTS: CD44 expression was not detected in either hepatocytes or biliary epithelial cells in normal livers. In sections from all 27 transplant hepatectomy specimens, CD44 was positive in bile duct epithelial cells but not in hepatocytes. The proportion of CD44+ ducts was much higher in biliary disease than in chronic hepatitis. By contrast, expression of HLA-DR was detected in a relatively small percentage of bile ducts. Activated, memory phenotype CD4+ T lymphocytes were increased in the parenchyma of all diseased livers and an infiltrate of activated CD8+ cells within the biliary epithelium was evident in inflammatory biliary disease. CONCLUSIONS: CD44 appears to play an important role in the development of autoimmune biliary disease by promoting lymphoepithelial interactions, whereas HLA-DR may be involved in the subsequent progression of these conditions.